ANALISIS PERANAN KOMITE SEKOLAH DALAM PENGAWASAN PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH MENENGAH PERTAMA (SMP) NEGERI DI KECAMATAN SEBERANG ULU I KOTA PALEMBANG - Fauziah Afriani (UNIVERSITAS INDO GLOBAL MANDIRI)
The purpose of this study was to determine and analyze the role of the School Committee in monitoring the use of school operational funds SMP in District Seberang Ulu I Palembang by using a qualitative approach and supported data kuantitatif.Peran School Committee in the use of funds is not yet fully refers to the dimensions the expected number of Kepmendiknas 44, 2002, namely: 1) as an institution consideration; 2) as a supporting institution; 3) as a control; and 4) as a mediator. Of 4 (four) the role of the School Committee, the only role as a board consideration and support institutions that have played by the Manager of School Committee in District Seberang Ulu I Palembang, while the role of the board and controllers as a mediator, Manager of School Committee in District Seberang Ulu Palembang I have not showed its role optimally. Key words : Role of the School Committee, BOS